Impact of sourdough fermentation on FODMAPs and amylase-trypsin inhibitor levels in wheat dough. (November 2022) - Boakye, Prince G.; Kougblenou, Ibilola; Murai, Takehiro; Okyere, Akua Y.; Anderson, James; Bajgain, Prabin; Philipp, Becky; LaPlante, Brian; Schlecht, Shannon; Vogel, Charlie; Carlson, Melissa; Occhino, Lorrene; et al.
Abstract: FODMAPs (fermentable oligo-, di-, and monosaccharides and polyols) and ATIs (Amylase-Trypsin inhibitors) have been reported to trigger intestinal symptoms in irritable bowel syndrome (IBS) patients and individuals with non-celiac wheat sensitivity (NCWS). The objective of this work was to investigate the FODMAP and ATI contents of 22 different wheat varieties grown in two locations in Minnesota, USA, and further study the effect of type I sourdough fermentation (4- and 12-h fermentation times) on the FODMAP and ATI levels in these varieties. FODMAPs and ATIs were quantified using High-performance anion-exchange chromatography (HPAEC) and High-performance liquid chromatography (HPLC), respectively. FODMAPs and ATIs were significantly influenced by variety as well as growing location. Longer sourdough fermentation time (12 h) caused up to 69%, 69%, and 41% reductions in fructans, raffinose, and ATIs, respectively, in the resulting sourdoughs. However, a substantial increase in mannitol (550%) was observed after sourdough fermentation. These results suggest that mannitol should be monitored in addition to other FODMAPs during type I sourdough fermentation, and strategies to reduce their levels during type I sourdough fermentation and in final products should be considered. Graphical abstract: Image 1 Highlights: The wheat varieties showed large variations in their FODMAP and ATI levels. Type I sourdough fermentation reduced fructan and raffinose levels in wheat dough. Type I sourdough fermentation reduced ATI levels in wheat dough. Type I sourdough fermentation resulted in high mannitol levels in wheat dough.